The Church and Politics in Chile Challenges to Modern Catholicism. - Smith, Brian H. (Princeton : Princeton University Press, 2014)
Clarifying the growing role of the Latin American Catholic Church as an agent of social change, Brian H. Smith discusses the prophetic function of the Chilean Church during the country's metamorphosis from Conservative to Christian Democratic to Marxist to repressive military regime. Originally published in 1982. The Princeton Legacy Library uses the latest print-on-demand technology to again make available previously out-of-print books from the distinguished backlist of Princeton University Press. These paperback editions preserve the original texts of these important bo.
Cover; Contents; Part I: Ideological and Institutional Dynamics of the Roman Catholic Church; 1. Changes and Challenges in Post-Vatican II Catholicism; Part II: The Church and Socioeconomic Reform; Part III : Christian-Marxist Rapprochement; Part IV: The Prophetic Role of the Church Under Authoritarianism; Index.
Print version record.
Keywords: Catholic Church -- Chile -- History -- 20th century; Church and state -- Chile -- History -- 20th century; Chile -- Politics and government -- 1920-1970.; Chile -- Politics and government -- 1970-1973.; Chile -- Politics and government -- 1973-1988.; POLITICAL SCIENCE / General; Catholic Church; Church and state; Politics and government; Chile; RELIGION / Christian Life / Social Issues; RELIGION / Christianity / General; 1900 - 1999; Electronic books; History